The sublime - Belpotti, Marco; Berger, John; Morley, Simon, 1958-; Whitechapel Art Gallery (London : Whitechapel Gallery ; Cambridge, Mass. : MIT Press, 2010)
Marina Abramovic; Joseph Beuys; Tacita Dean; Walter De Maria; AK Dolven; Olafur Eliasson; Jitka Hanzlova; Gary Hill; Susan Hiller; Shirazeh Houshiary; Anish Kapoor; Mike Kelley; Yves Klein; Richard Long; Gusav Metzger; Henri Michaux; Barnett Newman; Tony Oursler; Cornelia Parker; Gerhard Richter; Doris Salcedo; Lorna Simpson; Stelarc; Hiroshi Sugimoto; Fred Tomaselli; James Turell; Luc Tuymans; Bill Viola; Zhang Huan
The unpresentable -- Transcendence -- Nature -- Technology -- Terror -- The uncanny -- Altered states.
boek
Keywords: Sublime, The, in art; Art, Modern -- 20th century; Art, Modern -- 21st century